Bioinspired carbide-derived carbons with hierarchical pore structure for the adsorptive removal of mercury from aqueous solution - Fischer, C.; Oschatz, Martin; Nickel, W.; Leistenschneider, D.; Kaskel, Stefan; Brunner, Eike (Chemical Communications, 2017)
Biosilica of the diatom species Thalassiosira pseudonana is used as hard template for the synthesis of silicon carbide-derived carbons. The typical species-specific macroporous structure is retained during the nanocasting-chlorine treatment process and the resulting materials exhibit very high specific surface areas up to 2300 m2 g-1. Bioinspired carbons show very high capacities in mercury adsorption from aqueous solution compared to reference materials.
CRIS-Team Scopus Importer:2022-04-14